2017
DOI: 10.1097/mjt.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration and Acceleration Capacities in Risk Stratification for Arrhythmias in Patients With Chronic Obstructive Pulmonary Disease

Abstract: Patients with COPD associate a significant autonomic imbalance and a higher incidence of arrhythmias. DC could be a strong predictor for supraventricular and ventricular arrhythmias in patients with COPD with no clinically apparent cardiac disease. AC could be useful alongside with DC regarding the risk for ventricular arrhythmias, but seems to have lesser value as a predictor for supraventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…19 Buzea et al further evaluated the ability of DC to predict the development of arrhythmias in COPD patients; they also found a significant correlation between DC and the incidence of arrhythmias. 21 Based on the results of ROC curve analysis in our study, DRs were found to be a robust predictor of supraventricular and ventricular arrhythmias. Furthermore, different DRs (DR2, DR4, and DR8) demonstrated different sensitivity and specificity for predicting the incidence of different types of arrhythmias.…”
Section: Copdmentioning
confidence: 66%
See 1 more Smart Citation
“…19 Buzea et al further evaluated the ability of DC to predict the development of arrhythmias in COPD patients; they also found a significant correlation between DC and the incidence of arrhythmias. 21 Based on the results of ROC curve analysis in our study, DRs were found to be a robust predictor of supraventricular and ventricular arrhythmias. Furthermore, different DRs (DR2, DR4, and DR8) demonstrated different sensitivity and specificity for predicting the incidence of different types of arrhythmias.…”
Section: Copdmentioning
confidence: 66%
“…20 A recent study also found that DC can help stratify COPD patients based on their risk of arrhythmias. 21 However, the predictive value of DRs for risk stratification of COPD patients is yet to be clarified. In this study, we sought to evaluate the correlation of DRs with COPD and assess its application for predicting the occurrence of arrhythmias in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, DC index could reflect the cardiac vagal modulation on heart rate [7, 10, 13, 31, 32]. When applied PRSA to heartbeat intervals for assessing vagal tone modulation, the anchor points selected according to Eq.…”
Section: Discussionmentioning
confidence: 99%